Predicting the taxonomic and environmental sources of integron gene cassettes using structural and sequence homology of attC sites - Timothy M. Ghaly (Nature Portfolio, 2021)
Ghaly et al. use cassette recombination sites to predict the origins of antibiotic resistance cassettes spread by mobile integrons. They find that more than a quarter of all resistance cassettes have recombination sites that are structurally conserved among one of three taxa (Xanthomonadales, Spirochaetes and Vibrionales).